Task-Focused Summarization Of Email - Corston-Oliver, Simon H.; Ringger, Eric; Gamon, Michael; Campbell, Richard (Association for Computational Linguistics, 2004)
We describe SmartMail, a prototype system for automatically identifying action items (tasks) in email messages. SmartMail presents the user with a task-focused summary of a message. The summary consists of a list of action items extracted from the message. The user can add these action items to their " to do " list.